PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA, KOMPETENSI, DAN DISIPLIN KERJA TERHADAP KINERJA GURU SMP PGRI 6 KEDAWUNG SRAGEN - SL. Triyaningsih, Asta Wiyana, Alwi Suddin & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2016)
The results showed (1) leadership, not significant effect on the SMP PGRI 6 Kedawung Sragen, the first hypothesis is proven true. (2) work environment significant effect on the SMP PGRI 6 Kedawung Sragen. Thus the second hypothesis is accepted or proven true. (3) competention of teacher Discipline work is significant effect on the SMP PGRI 6 Kedawung Sragen, the third hypothesis is proven true. (4) The effect of a significant style of leadership, work environment, competention of teacher and discipline work together on employee performance in the SMP PGRI 6 Kedawung Sragen of Adjusted R2 value of 0,752 (75,2%) of the remaining 34,8% influenced by other variables outside the research model, meaning 4th hypothesis proved to be true. (5) The results of this study indicate that the determinants of employee performance SMP PGRI 6 Kedawung Sragen is leadership, as well as the most dominant variables influence the employee's performance means that the hypothesis to 5 proved to be true.Keywords: leadership; work environment, competention of teacher; work discipline, employee performance.